Hizmet in Transitions European Developments of a Turkish Muslim-Inspired Movement - Weller, Paul (Springer Nature, 2022)
In this open-access monograph, Paul Weller explores how the movement known as Hizmet (meaning "service") is undergoing a period of transitions in Europe. Inspired by the teaching and practice of the Turkish Islamic scholar, Fethullah Gülen, Hizmet has been active in Europe (and other continents) for several decades. It has always been subject to some degree of contestation, which has intensified following the July 2016 coup attempt in Turkey, for which the current Turkish government holds Fethullah Gülen and Hizmet as responsible - a claim they strongly deny. In Turkey, thousands of people associated with Hizmet have been imprisoned. In Europe, pressures have been brought to bear on the movement and its activities. In charting a way forward, Hizmet finds itself in a significant transitional period, the nature and possible future trajectories of which are explored in this volume. The book is informed by a comprehensive literature review and a recent research project which includes primary research interviews with key Hizmet figures in Europe and beyond. It contends that to properly understand Hizmet in Europe, one has to situate it in its interactive engagement both with its diverse European national contexts and with Fethullah Gülen's teaching and practice.